Non-graphitized carbon/Cu2O/Cu0 nanohybrids with improved stability and enhanced photocatalytic H2 production - Areti Zindrou; Loukas Belles; Maria Solakidou; Nikos Boukos; Yiannis Deligiannakis (Scientific Reports, 2023)
Abstract Cu2O is a highly potent photocatalyst, however photocorrosion stands as a key obstacle for its stability in photocatalytic technologies. Herein, we show that nanohybrids of Cu2O/Cu0 nanoparticles interfaced with non-graphitized carbon (nGC) constitute a novel synthesis route towards stable Cu-photocatalysts with minimized photocorrosion. Using a Flame Spray Pyrolysis (FSP) process that allows synthesis of anoxic-Cu phases, we have developed in one-step a library of Cu2O/Cu0 nanocatalysts interfaced with nGC, optimized for enhanced photocatalytic H2 production from H2O. Co-optimization of the nGC and the Cu2O/Cu0 ratio is shown to be a key strategy for high H2 production, > 4700 μmoles g−1 h−1 plus enhanced stability against photocorrosion, and onset potential of 0.234 V vs. RHE. After 4 repetitive reuses the catalyst is shown to lose less than 5% of its photocatalytic efficiency, while photocorrosion was < 6%. In contrast, interfacing of Cu2O/Cu0 with graphitized-C is not as efficient. Raman, FT-IR and TGA data are analyzed to explain the undelaying structural functional mechanisms where the tight interfacing of nGC with the Cu2O/Cu0 nanophases is the preferred configuration. The present findings can be useful for wider technological goals that demand low-cost engineering, high stability Cu-nanodevices, prepared with industrially scalable process.